ANALISIS OPTIMASI KEUNTUNGAN PRODUKSI DONAT DENGAN MENGGUNAKAN LINEAR PROGRAMMING MELALUI METODE SIMPLEKS (Studi Kasus pada Abata Donuts di Surakarta) - Ade Nelsa Yusnaini; Erni Widajanti; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study is: 1) Identify the optimum amount of donut products that must be produced by the Abata Donuts company in Surakarta. 2) Analyze whether each type of donut product produced so far has achieved maximum profit. 3) Analyzing the efficiency of input use in producing donuts. 4) Analyzing the results of the application of linear programming with the simplex method in influencing changes in the benefits of each type of donut and changes in the value of the resources they have to the optimum results. This type of research uses a simplex method of linear programming method by the Abata Donuts Company. The type of data uses qualitative and quantitative data. Data sources use primary and secondary data. Data analysis techniques using Qm software for Windows 5. The results of the calculation of linear simplex programming indicate that the production of Abata Donat has increased. Analysis of the results of profit optimization using linear programming simplex that may occur at the destination coefficient based on the optimum results that the number of types of donuts produced in Abata Donuts.